Severity of presentation is associated with time to recovery in spinal epidural lipomatosis. Issue 8 (August 2015) - Praver, Moshe; Kennedy, Benjamin C.; Ellis, Jason A.; D'Amico, Randy; Mandigo, Christopher E.
Abstract We present a patient with prednisone-induced spinal epidural lipomatosis (SEL) and relatively acute neurologic deterioration followed by rapid recovery after surgical decompression. SEL is a rare disease characterized by hypertrophy of epidural fat, most commonly associated with exogenous steroid use. To our knowledge, an analysis of the dynamics of steroid dose related to time to onset has never been performed, or of patient presentation features with respect to patient outcome. We retrospectively reviewed the literature for English language series and case reports of SEL associated with prednisone use from 1975–2013. Data were compiled for 41 patients regarding the prescribed dose of prednisone and length of treatment, as well as the severity of symptoms on the Ranawat scale, time to onset, time to recovery, and degree of recovery of neurological symptoms. Fisher's exact test and analysis of variance were used for comparing proportions, and p values <0.05 were considered statistically significant. We found that the mean cumulative dose of prednisone trended towards an association with a lack of recovery (p = 0.06) and may be related to rate of recovery. Prescribed prednisone dose varied inversely with the time before onset of neurological symptoms, but failed to reach statistical significance. Higher severity of presenting symptoms on the Ranawat scale were found to be associated with a higher likelihood of delayed recovery (p = 0.035). Patients with symptoms lower on the Ranawat scale more frequently experienced complete neurologic recovery, though this did not reach significance. The acuity of neurological deterioration was not related to the time to recovery or ultimate degree of recovery. Severity of presentation on the Ranawat scale is associated with rate of recovery and may be related to degree of recovery in SEL patients. Cumulative dose of prednisone may be related to degree and rate of recovery. Prescribed dose of prednisone may be related to time to onset of neurological symptoms. Acuity of neurological deterioration is not related to rate or degree of recovery.